Piezofilm yarn sensor-integrated knitted fabric for healthcare applications - TUNÇAY ATALAY, ASLI (SAGE PUBLICATIONS INC, 2017)
Continuous measurement of cardio-respiratory signals offers various kinds of information valuable for the diagnosis of disease and management of the disease process. The article reports the development of the Piezofilm yarn sensor for healthcare applications, and investigates its performance by monitoring cardio-respiratory signals of human body over an extended period of time. Piezofilm yarn sensor was developed by embedding the thin PVDF strips within the textile yarn. The working mechanism of the Piezofilm yarn sensor is based on voltage generation due to the applied stress. In order to deploy the Piezofilm yarn sensor in the application environment, it was integrated into the knitted textile fabric and then sewn to form belt to be placed at the chest wall and wrist area. The raw signals were acquired through the Piezofilm lab amplifier, National Instrument data acquisition device and SignalExpress software. Fast Fourier Transform analysis was performed to calculate the average cardio-respiratory signal frequencies. Based on Fast Fourier Transform analysis, an additional signal-processing step was added to eliminate the unwanted mechanical interference and body signals by using an Infinite Impulse Response band pass filter. The Piezofilm yarn sensor embedded sensing fabric was able to measure both respiratory rate and heart beat rate under static and dynamic conditions. The wrist area measurements for heart beat signals were found to be more uniform in comparison to the chest area measurements. Apart from the general healthcare, this sensing fabric could also be used in studies related to biorhythms, sports, detection of sleep apnea and heart problems.
Keywords: Sensors; electronic textiles; piezoelectric PVDF; cardio-respiratory monitoring; piezofilm yarn sensor; pieozofilm yarn sensor fabric; STRAIN SENSOR; DESIGN; FIBER; PARAMETERS; FILM